2007
DOI: 10.2174/138620707782152353
|View full text |Cite
|
Sign up to set email alerts
|

Response of DNA Fragments to Potentiometric Sensors Studied Using HPLC

Abstract: Potentiometric sensors are studied as viable candidates for the construction of high throughput DNA arrays. For preliminary investigations, such sensors were used in an HPLC setup in the present work. This avoided errors due to ionic contaminants or additives in the commercial samples. The oligonucleotides dT(10), dT(20) and dT(30) were used as test substances. The potentiometric sensors were of the coated wire type, containing PVC, DOP, MTDDACl and a synthetic podand urea receptor. The HPLC system consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Also large biomolecules can be used as analyte (prey ligand). From our experiences with oligonucleotides, 10 we know that these multiply charged molecules give very good potentiometric responses. As an example, the 22-mer 5′-AAAATATCATCTTTGGTGTTTC-3′ yields a slope (S, eqs 2 and 3) value of 38 mV per decade, which is much higher than calculated by the Nernst equation (eq 2).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also large biomolecules can be used as analyte (prey ligand). From our experiences with oligonucleotides, 10 we know that these multiply charged molecules give very good potentiometric responses. As an example, the 22-mer 5′-AAAATATCATCTTTGGTGTTTC-3′ yields a slope (S, eqs 2 and 3) value of 38 mV per decade, which is much higher than calculated by the Nernst equation (eq 2).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The market for such sensors is very extensive, and especially for biomedical and microbiological research, they are part of highly automated equipment with high sample throughput. Several groups have shown that it is possible to use them for targeting charged organic molecules, , multiply charged polymeric and oligomeric substances, , and even bioparticles . In the present paper, we will show that potentiometric sensors of the “coated wire” type often respond to the analytes according to pure adsorption kinetics controlled phenomena.…”
mentioning
confidence: 99%